An exploratory study on the influence of student-centered teaching methods on student motivation towards education - Julies, Auldrin (The Independent Institute of Education, 2020)
Change is a constant within the educational process with the ever-evolving design of subject matter, change in the dynamics within classrooms, and changes within teaching strategies implemented by educators (Hansen & Laverty, 2010). This is all done in an attempt to reform educational practices to create learning environments that will stimulate student engagement towards subject matter and further encourage them to become capable graduates, that are able to adapt to the workforce and contribute towards the advancement of the industry (Cudney and Ezzel, 2017). The study aimed to establish the value student-centered approaches had on the students’ motivation towards learning and find the most effective approach for educators to create learning environments that will allow for significant learning experience to take place. According to Fink (2013), higher education needs to become more meaningful to the student through educational reform and challenging conventional practices. The dire need for the South African higher education system to produce competent graduates has become crucial towards the advancement and survival of the country’s economy (Mdepa and Tshiwula, 2012). With the increasing popularity of student-centered teaching within classrooms, the focus has shifted from teacher to student (McKenna, 2013). This has challenged higher education institutions to create learning environments that will develop key skills and knowledge within the student, which can be applied to the real-world environment. This has seen a rise in student centered teaching methods such as constructivism, that encourages student interaction and sharing of feelings, beliefs, and experience to construct new knowledge. One of the many benefits of student-centered teaching is that it encourages interaction. According to Trolian (2019) many students participate in non-academic activities on campuses to build self-confidence, as research showed a direct link between social interaction and how it leads to better academic results. South African higher education faces many challenges that are unique to its socioeconomic context. Mckenna (2013) argued that for student-centered teaching to successfully be integrated into South African classrooms, there needs to be a clear understanding of the type of student and their needs. The study allowed for the exploration on how educators can utilize student-centered teaching approaches to more effectively motivate the learners to interact with peers and engage with subject matter. The research involved a logical process that firstly involved conducting a review of literature, that allowed for a holistic review of student-centered teaching approaches and its effectiveness within higher education classrooms. The literature provided some critical comparisons between traditional teacher-centered methods and student-centered teaching. It was followed by a critical research investigation, through exposing students at eta College to both teacher and student-centered teaching methods. Students were able to engage through both mediums of delivery to measure if the teaching method had a distinct contribution towards student motivation. The literature focused on both student and teacher-centered practices to identify its effectiveness within higher education. The research looked at traditional teaching approaches and the advantages and disadvantages of employing its use within current higher education classrooms. It was important to identify the past, present and future teaching approaches, and its impact on student motivation. The review of literature was expanded towards student-centered teaching approaches within higher education and its value towards student engagement. The research looked at which of these approaches had the best potential of producing a self-autonomous learner and a graduate that will be able to fully function in the workforce while contributing to the advancement of the industry. The study aimed to address questions around students’ taking an active role in the learning process to enhance motivation. The research study was conducted through identifying a sample group of Sport Management students currently studying at Pretoria eta College. The sample group only included second and third-year students, as these groups could further draw from past exposure to various teaching methods used throughout their years studying at eta College. The students were provided with qualitative questionnaires to gain a deeper understanding of factors influencing their learning experience. The study sample was firstly exposed to a traditional theory orientated class, where the educator was the central figure within the learning environment. Students were then exposed to a practical student-centered teaching session where they were responsible for learning and the process relied immensely on their interaction with peers in constructing own understanding of key concepts. Preliminary results concluded that there was a direct link between active learning strategies and its impact on student’s enjoyment of the educational process. There was however a greater preference amongst third year students for practical student-centered approaches to teaching, whereas second year students still showed some interest in teacher-centric approaches. This was a key indicator that students at a higher level within the educational process starts showing a greater interest in how to apply their knowledge to solve real-world issues, as they are at the phase of entering into the workforce.
Keywords: Teacher-centered approaches; Student-centered approaches; Student motivation